Nonlinear Compensator Design For Bilinear Systems - Foo, Mathias Fui Lin (2004)
There are many processes, which inherit the behaviour of a bilinear system. Bilinear systems can be considered as a variation of linear system due to their many similarities with the latter. Despite being treated as a variation of linear systems, the effect of the nonlinearities is still distinctive. Hence, there arises a need to compensate for these nonlinearities. This leads to the non linear compensator design issues for bilinear systems.